Theology, Reason, and Science Beyond Syntesis: Constructing a Third Space of Islamic Knowledge in Colonial Minangkabau - Rais, Zaim; Syukri, Ahmad; Ashadi, Andri; Hadi, Rahmad Tri (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2026)
This study examines how Ibrahim Musa Parabek (1883-1963) integrated theology, rationalism, and empirical science within the colonial intellectual context of early twentieth-century Minangkabau. Departing from dichotomous and synthetic frameworks that dominate existing scholarship on Islamic modernism, this paper argues that his epistemological project constitutes a structured form of epistemic hybridity produced within a localized Third Space. Drawing on Bhabha’s theoretical apparatus of hybridity, mimicry, and Third space, and employing thematical-content analysis of primary texts, historical-contextual reconstruction, and hermeneutic-philosophical synthesis, this study identifies three operative mechanisms in Ibrahim’s thought: domain differentiation (taqsīm al-majāl), hierarchical ordering of knowledge sources (tartīb), and functional mimicry of rational-scientific procedures. Analysis of Ijābat al-Sūl, Hidāyat al-Ṣibyān, and Thawalib Parabek teaching manuscripts demonstrates that reason was granted bounded cognitive authority in worldly domains while revelation retained exclusive normative jurisdiction. These findings reconceptualize hybridity as epistemic modulation, reframe Thawalib Parabek as a productive institution of Islamic knowledge production, and demonstrate that alternative modernities can be constructed from within Islamic doctrinal traditions without compromising their foundational premises.